A sodium ion battery hard carbon-molybdenum disulfide negative electrode material and preparation method thereof

The carbon material is coated with molybdenum disulfide to prepare a hard carbon-molybdenum disulfide negative electrode material, which solves the problem of poor circulation performance of molybdenum disulfide negative electrode material in the prior art, and significantly improves the circulation performance of sodium ion batteries.

CN115332503BActive Publication Date: 2025-04-08SICHUAN BAISHIGE NEW ENERGY CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210928908.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-03
Publication Date
2025-04-08
Estimated Expiration
2042-08-03

AI Technical Summary

Technical Problem

In the prior art, molybdenum disulfide is poor in circulation performance when used as the negative electrode material of sodium ion battery, resulting in poor circulation performance of the battery.

Method used

Molybdenum disulfide is coated by carbon material to prepare a hard carbon-molybdenum disulfide negative electrode material to improve its circulation performance. The specific steps include reacting the molybdenum source with the sulfur source to form molybdenum disulfide, then mixing it with the carbon source and sintering it at high temperature to form a structure coated with a hard carbon material.

Benefits of technology

The conductive properties of the negative electrode material are improved through hard charcoal coating, avoiding excessive expansion rate during sodium storage and powdering during circulation, and significantly improving the circulation performance of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115332503B_ABST
    Figure CN115332503B_ABST
Patent Text Reader

Abstract

The present invention provides a sodium ion battery hard carbon-molybdenum disulfide negative electrode material and a preparation method thereof, which relates to the technical field of sodium ion batteries. The preparation method comprises the following steps: dissolving a molybdenum source and a sulfur source in a solvent, mixing to obtain a mixed solution; spray drying the mixed solution to obtain a molybdenum disulfide precursor; sintering the molybdenum disulfide precursor under the protection of an argon-hydrogen mixed gas to obtain molybdenum disulfide; mixing a carbon source with molybdenum disulfide, adding ethylene tar, and sintering to obtain a sodium ion battery hard carbon-molybdenum disulfide negative electrode material. The preparation method of the sodium ion battery hard carbon-molybdenum disulfide negative electrode material provided by the present invention first generates molybdenum disulfide by reacting a molybdenum source with a sulfur source, then mixing and sintering the carbon source with molybdenum disulfide to obtain a structure of molybdenum disulfide coated with a hard carbon material, which improves the electrical conductivity on the one hand, and avoids excessive expansion rate during sodium storage on the other hand, thereby improving the cycle performance of the sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium ion battery hard carbon-molybdenum disulfide negative electrode material and a preparation method thereof. Background Art

[0002] Compared with lithium-ion batteries, sodium-ion batteries have more abundant raw material sources and lower costs, so they have more commercial advantages than lithium-ion batteries. Because sodium ions have a larger ionic radius than lithium ions, the negative electrode materials commonly used in lithium-ion batteries are not suitable for sodium-ion batteries. Finding negative electrode materials suitable for sodium-ion batteries is a technical problem that needs to be solved urgently to promote the commercialization of sodium-ion batteries.

[0003] Among them, molybdenum disulfide (MoS2) has a large interlayer spacing and weak interlayer van der Waals force, and has low resistance to sodium ion insertion and extraction. Therefore, MoS2 has a higher specific capacity as the negative electrode of sodium ion batteries; however, MoS2 has poor conductivity, and after forming an alloy with Na, its expansion rate is too high, and it is easy to pulverize during the cycle process, resulting in poor battery cycle performance. Summary of the invention

[0004] The technical problem to be solved by the present invention is: in order to solve the problem of poor cycle performance when molybdenum disulfide is used as a negative electrode material for sodium ion batteries in the prior art, the present invention provides a method for preparing a hard carbon-molybdenum disulfide negative electrode material for sodium ion batteries. The preparation method improves the cycle performance of the negative electrode material by coating molybdenum disulfide with a carbon material, thereby solving the problem of poor cycle performance when molybdenum disulfide is used as a negative electrode material for sodium ion batteries in the prior art.

[0005] The technical solution adopted by the present invention to solve its technical problem is:

[0006] A method for preparing a sodium ion battery hard carbon-molybdenum disulfide negative electrode material comprises the following steps:

[0007] S1: dissolving a molybdenum source and a sulfur source in a solvent, mixing, and obtaining a mixed solution;

[0008] S2: spray drying the mixed solution at 150° C. to 220° C. to obtain a molybdenum disulfide precursor;

[0009] S3: sintering the molybdenum disulfide precursor at 300° C. to 500° C. under the protection of an argon-hydrogen mixed gas to obtain molybdenum disulfide;

[0010] S4: mixing the carbon source with the molybdenum disulfide, adding ethylene tar, and sintering at 700° C. to 900° C. under the protection of an argon-hydrogen mixed gas to obtain a sodium ion battery hard carbon-molybdenum disulfide negative electrode material.

[0011] Optionally, the molybdenum source is selected from at least one of ammonium molybdate, magnesium molybdate, lithium molybdate and potassium molybdate.

[0012] Optionally, the sulfur source is selected from at least one of ammonium thiocyanate, ammonium sulfide, sodium sulfide, potassium sulfide, sodium thiosulfate, diallyl sulfide, ethyl mercaptan, propyl mercaptan, and thiophenol.

[0013] Optionally, the solvent is deionized water or ethanol.

[0014] Optionally, the carbon source is selected from at least one of starch, lignin, cellulose and humic acid powder.

[0015] Optionally, the molar ratio of the molybdenum source to the sulfur source is in the range of 1:(1-1.5).

[0016] Optionally, the mass ratio of the carbon source to the molybdenum disulfide is in the range of (1-5):1.

[0017] Optionally, sintering the molybdenum disulfide precursor at 300° C. to 500° C. includes: heating to 300° C. to 500° C. at a heating rate of 5 to 10° C. / min and sintering for 1 hour.

[0018] Optionally, sintering at 700° C. to 900° C. in step S4 includes: heating to 700° C. to 900° C. at a heating rate of 5 to 10° C. / min and sintering for 1 hour.

[0019] Another object of the present invention is to provide a sodium ion battery hard carbon-molybdenum disulfide negative electrode material, which is prepared by the preparation method of the sodium ion battery hard carbon-molybdenum disulfide negative electrode material as described above.

[0020] The beneficial effects of the present invention are:

[0021] The method for preparing a sodium ion battery hard carbon-molybdenum disulfide negative electrode material provided by the present invention comprises the following steps: firstly, molybdenum disulfide is generated by reacting a molybdenum source with a sulfur source, and then a carbon source and the molybdenum disulfide are mixed and sintered to obtain a structure in which molybdenum disulfide is coated with a hard carbon material. On the one hand, the conductivity is improved by the hard carbon material coated on the outside of the molybdenum disulfide, and on the other hand, an excessively high expansion rate during sodium storage and pulverization during circulation are avoided, thereby improving the cycle performance of the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0023] Figure 1 This is a TEM photo of the sodium ion battery hard carbon-molybdenum disulfide negative electrode material prepared in Example 1 of the present invention;

[0024] Figure 2This is the first charge and discharge curve of the hard carbon-molybdenum disulfide negative electrode material for a sodium ion battery prepared in Example 1 of the present invention;

[0025] Figure 3 This is the cycle curve of the hard carbon-molybdenum disulfide negative electrode material for sodium ion batteries prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0026] The present invention is now further described in detail. The embodiments described below are exemplary and intended to be used to explain the present invention, but cannot be understood as limiting the present invention. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention belong to the scope of protection of the present invention.

[0027] In order to solve the problem of poor cycle performance when molybdenum disulfide is used as a negative electrode material for sodium ion batteries in the prior art, the present invention provides a method for preparing a hard carbon-molybdenum disulfide negative electrode material for sodium ion batteries, and the preparation method comprises the following steps:

[0028] S1: dissolving a molybdenum source and a sulfur source in a solvent, mixing, and obtaining a mixed solution;

[0029] S2: spray drying the mixed solution at 150° C. to 220° C. to obtain a molybdenum disulfide precursor;

[0030] S3: sintering the molybdenum disulfide precursor at 300° C. to 500° C. under the protection of an argon-hydrogen mixed gas to obtain molybdenum disulfide;

[0031] S4: Mix the carbon source with molybdenum disulfide, add ethylene tar, and sinter at 700°C to 900°C under the protection of argon-hydrogen mixed gas to obtain a hard carbon-molybdenum disulfide negative electrode material for a sodium ion battery.

[0032] The present invention provides a method for preparing a hard carbon-molybdenum disulfide negative electrode material for a sodium ion battery. First, molybdenum disulfide is generated by reacting a molybdenum source with a sulfur source, and then a carbon source and molybdenum disulfide are mixed and sintered to obtain a structure in which molybdenum disulfide is coated with a hard carbon material. Ethylene tar is a cheap petrochemical byproduct. As a liquid carbon source, it can be fully mixed with sulfide for coating. After carbonization, a core-shell structure of hard carbon-coated molybdenum disulfide is generated. Since the hard carbon layer spacing is large and the volume change after sodium insertion is small, the hard carbon coating can significantly inhibit the expansion and contraction of molybdenum disulfide during the charge and discharge process and extend the cycle life. On the one hand, the conductivity is improved by the hard carbon material coated on the outside of the molybdenum disulfide, and on the other hand, the expansion rate is prevented from being too high during sodium storage and pulverization during the cycle, thereby improving the cycle performance of the sodium ion battery.

[0033] In order to ensure the comprehensive performance of the hard carbon-molybdenum disulfide negative electrode material of the sodium ion battery, the present invention preferably selects at least one of the molybdenum source from ammonium molybdate, magnesium molybdate, lithium molybdate, and potassium molybdate; the sulfur source is selected from at least one of ammonium thiocyanate, ammonium sulfide, sodium sulfide, potassium sulfide, sodium thiosulfate, diallyl sulfide, ethanethiol, propylthiol, and thiophenol; and the solvent is preferably deionized water or ethanol.

[0034] The present invention obtains nano-scale molybdenum disulfide by uniformly mixing the liquid phase and then spray drying and granulating, which can effectively improve the volume change effect of molybdenum disulfide during charging and discharging. At the same time, nano-sizing is beneficial to shortening the diffusion path of ions and electrons in the reaction process of sodium ions and molybdenum disulfide, thereby improving the rate performance of molybdenum disulfide.

[0035] Furthermore, during the preparation of molybdenum disulfide, an argon-hydrogen mixed gas is used for protection so as to ensure that the sulfide is not oxidized by the reducing atmosphere. The preferred volume content of hydrogen in the argon-hydrogen mixed gas is 5%-10%.

[0036] In order to improve the sodium insertion capacity and cycle life of the negative electrode material, the present invention preferably uses a carbon source selected from at least one of starch, lignin, cellulose, and humic acid powder.

[0037] In order to ensure the comprehensive performance of the negative electrode material, the present invention preferably has a molar ratio of the molybdenum source to the sulfur source in the range of 1:(1-1.5); a mass ratio of the carbon source to molybdenum disulfide in the range of (1-5):1, and preferably has a mass ratio of ethylene tar to molybdenum disulfide in the range of (10-20):1.

[0038] To ensure that the prepared hard carbon-molybdenum disulfide negative electrode material can be suitable for sodium ion batteries, the present invention preferably sinters the molybdenum disulfide precursor at 300°C to 500°C, including: heating to 300°C to 500°C at a heating rate of 5 to 10°C / min and sintering for 1 hour; preferably, sintering at 700°C to 900°C in step S4 includes: heating to 700°C to 900°C at a heating rate of 5 to 10°C / min and sintering for 1 hour.

[0039] Another object of the present invention is to provide a sodium ion battery hard carbon-molybdenum disulfide negative electrode material, which is prepared by the preparation method of the sodium ion battery hard carbon-molybdenum disulfide negative electrode material as described above.

[0040] The hard carbon-molybdenum disulfide negative electrode material for sodium ion batteries provided by the present invention has a structure in which molybdenum disulfide is coated with a hard carbon material. On the one hand, the conductivity is improved by the hard carbon material coated on the outside of the molybdenum disulfide. On the other hand, an excessively high expansion rate during sodium storage and pulverization during circulation are avoided, thereby improving the cycle performance of the sodium ion battery.

[0041] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below.

[0042] Example 1

[0043] This embodiment provides a method for preparing a hard carbon-molybdenum disulfide negative electrode material for a sodium ion battery, the preparation method comprising the following steps:

[0044] S1: dissolving ammonium molybdate and sodium thiosulfate in a molar ratio of 1:1 in deionized water, stirring evenly to obtain a mixed solution;

[0045] S2: spray drying the mixed solution at 220° C. to obtain a molybdenum disulfide precursor;

[0046] S3: Under the protection of argon-hydrogen mixed gas, the temperature is raised to 500°C at a heating rate of 5°C / min and sintered for 1 hour to obtain molybdenum disulfide;

[0047] S4: Mix starch and molybdenum disulfide in a mass ratio of 3:1, add ethylene tar, the mass ratio of ethylene tar to molybdenum disulfide is 10:1, stir and mix evenly, and under the protection of argon-hydrogen mixed gas, heat the mixture to 850°C at a heating rate of 8°C / min and sinter for 1 hour to obtain a sodium ion battery hard carbon-molybdenum disulfide negative electrode material.

[0048] See also Figure 1-Figure 3 As shown, the obtained sodium ion battery hard carbon-molybdenum disulfide negative electrode material was tested, wherein Figure 1 The dark particles in the figure are molybdenum disulfide. The performance test data of the hard carbon negative electrode material as a negative electrode material for sodium ion batteries are shown in Table 1.

[0049] Example 2

[0050] This embodiment provides a method for preparing a hard carbon-molybdenum disulfide negative electrode material for a sodium ion battery, the preparation method comprising the following steps:

[0051] S1: dissolving potassium molybdate and ammonium thiocyanate in a molar ratio of 1:1.1 in ethanol, stirring evenly to obtain a mixed solution;

[0052] S2: spray drying the mixed solution at 150° C. to obtain a molybdenum disulfide precursor;

[0053] S3: Under the protection of argon-hydrogen mixed gas, the temperature is raised to 400°C at a heating rate of 8°C / min and sintered for 1 hour to obtain molybdenum disulfide;

[0054] S4: Mix lignin and molybdenum disulfide in a mass ratio of 2:1, add ethylene tar, the mass ratio of ethylene tar to molybdenum disulfide is 15:1, stir and mix evenly, and under the protection of argon-hydrogen mixed gas, heat the mixture to 700°C at a heating rate of 5°C / min and sinter for 1 hour to obtain a sodium ion battery hard carbon-molybdenum disulfide negative electrode material.

[0055] The obtained hard carbon-molybdenum disulfide negative electrode material for sodium ion battery was tested. The performance test data of the hard carbon negative electrode material as a negative electrode material for sodium ion battery are shown in Table 1.

[0056] Example 3

[0057] This embodiment provides a method for preparing a hard carbon-molybdenum disulfide negative electrode material for a sodium ion battery, the preparation method comprising the following steps:

[0058] S1: dissolving magnesium molybdate and ethanethiol in a molar ratio of 1:1.5 in ethanol, stirring evenly to obtain a mixed solution;

[0059] S2: spray drying the mixed solution at 180° C. to obtain a molybdenum disulfide precursor;

[0060] S3: Under the protection of argon-hydrogen mixed gas, the temperature is raised to 500°C at a heating rate of 10°C / min and sintered for 1 hour to obtain molybdenum disulfide;

[0061] S4: Mix humic acid powder and molybdenum disulfide in a mass ratio of 4:1, add ethylene tar, the mass ratio of ethylene tar to molybdenum disulfide is 20:1, stir and mix evenly, and under the protection of argon-hydrogen mixed gas, heat the temperature to 900°C at a heating rate of 10°C / min and sinter for 1h to obtain a sodium ion battery hard carbon-molybdenum disulfide negative electrode material.

[0062] The obtained hard carbon-molybdenum disulfide negative electrode material for sodium ion battery was tested. The performance test data of the hard carbon negative electrode material as a negative electrode material for sodium ion battery are shown in Table 1.

[0063] Comparative Example 1

[0064] This comparative example provides a method for preparing a hard carbon negative electrode material for a sodium ion battery, the preparation method comprising the following steps:

[0065] The starch was heated to 850°C at a heating rate of 8°C / min and sintered for 1 hour under the protection of an argon-hydrogen mixed gas to obtain a hard carbon negative electrode material for a sodium ion battery.

[0066] The obtained hard carbon negative electrode material for sodium ion batteries was tested, and the performance test data of the hard carbon negative electrode material when used as a negative electrode material for sodium ion batteries is shown in Table 1.

[0067] Comparative Example 2

[0068] This comparative example provides a method for preparing a sodium ion battery molybdenum disulfide negative electrode material, the preparation method comprising the following steps:

[0069] S1: dissolving ammonium molybdate and sodium thiosulfate in a molar ratio of 1:1 in deionized water, stirring evenly to obtain a mixed solution;

[0070] S2: spray drying the mixed solution at 220° C. to obtain a molybdenum disulfide precursor;

[0071] S3: Under the protection of argon-hydrogen mixed gas, the temperature is raised to 500°C at a heating rate of 5°C / min and sintered for 1 hour to obtain molybdenum disulfide, i.e., molybdenum disulfide negative electrode material for sodium ion batteries.

[0072] The obtained sodium ion battery molybdenum disulfide negative electrode material was tested, and the performance test data of the molybdenum disulfide negative electrode material when used as a sodium ion battery negative electrode material is shown in Table 1.

[0073] Comparative Example 3

[0074] This comparative example provides a method for preparing a hard carbon negative electrode material for a sodium ion battery, the preparation method comprising the following steps:

[0075] S1: dissolving ammonium molybdate, sodium thiosulfate and starch in deionized water, adding ethylene tar and stirring evenly to obtain a mixed solution; wherein the molar ratio of ammonium molybdate to sodium thiosulfate is 1:1, the mass ratio of starch to ammonium molybdate is 3:1.2, and the mass ratio of ethylene tar to molybdenum disulfide is 10:1;

[0076] S2: spray drying the mixed solution at 220°C to obtain a precursor;

[0077] S3: Under the protection of argon-hydrogen mixed gas, the temperature was raised to 850°C at a heating rate of 8°C / min and sintered for 1 hour to obtain a hard carbon negative electrode material for a sodium ion battery.

[0078] See also Figure 1-Figure 3 As shown, the obtained sodium ion battery hard carbon negative electrode material was tested, wherein Figure 1 The dark particles in the figure are molybdenum disulfide. The performance test data of the hard carbon negative electrode material as a negative electrode material for sodium ion batteries are shown in Table 1.

[0079] Comparative Example 4

[0080] This comparative example provides a method for preparing a hard carbon negative electrode material for a sodium ion battery, the preparation method comprising the following steps:

[0081] S1: mixing molybdenum dioxide powder and sulfur powder in a mass ratio of 10:7 in a pulverizer to obtain a mixed raw material;

[0082] S2: putting the mixed raw materials into a crucible, placing it in a microwave tube atmosphere furnace under argon protection for microwave heating, keeping the temperature at 450° C. for 200 min, and then cooling it naturally to room temperature to obtain molybdenum disulfide;

[0083] S3: Mix starch and molybdenum disulfide in a mass ratio of 3:1, add ethylene tar, the mass ratio of ethylene tar to molybdenum disulfide is 10:1, stir and mix evenly, and under the protection of argon-hydrogen mixed gas, heat the mixture to 850°C at a heating rate of 8°C / min and sinter for 1 hour to obtain a hard carbon negative electrode material for a sodium ion battery.

[0084] Table 1

[0085]

[0086] It can be seen from the above data that the sodium ion hard carbon negative electrode materials prepared in various embodiments of the present invention have excellent long cycle life on the basis of good electrical properties.

[0087] In Comparative Example 1, the hard carbon obtained by sintering starch as a carbon source is used as the negative electrode material of the sodium ion battery. Compared with the solution provided by the present invention, the specific capacity of the pure hard carbon provided by this comparative example is difficult to exceed 280 mAh / g, which is much lower than the negative electrode material provided in the embodiment.

[0088] Comparative Example 2 directly uses molybdenum disulfide prepared according to the method of the present invention as the negative electrode material of the sodium ion battery. Compared with the solution provided by the present invention, although molybdenum disulfide has a high sodium insertion capacity, due to its poor conductivity and large sodium insertion volume expansion, it causes the electrode to be pulverized, the reversible capacity is low, and the cycle life is poor.

[0089] Compared with Example 1, in Comparative Example 3, the molybdenum source, the sulfur source and the carbon source are directly mixed to prepare the hard carbon negative electrode material. Compared with Example 1, the carbon source is mixed before the synthesis of nano-molybdenum disulfide, which hinders the reaction of molybdenum disulfide, resulting in the failure of the molybdenum source and the sulfur source to be effectively converted into molybdenum disulfide with sodium embedding activity, affecting the capacity.

[0090] Compared with Example 1, Comparative Example 4 changes the preparation process of molybdenum disulfide. Compared with Example 1, molybdenum disulfide is synthesized as a solid phase mixture, and the contact of the molybdenum disulfide reactants is insufficient, resulting in the failure of the molybdenum source and the sulfur source to be effectively converted into molybdenum disulfide with sodium embedding activity, and the generated reactants are micron-structured, not nano-structured, and the diffusion radius of electrons and ions during the charge and discharge process is large, which affects the capacity.

[0091] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A method for preparing a sodium ion battery hard carbon-molybdenum disulfide negative electrode material, characterized in that: The steps include: S1: dissolving a molybdenum source and a sulfur source in a solvent, mixing, and obtaining a mixed solution; S2: spray drying the mixed solution at 150° C. to 220° C. to obtain a molybdenum disulfide precursor; S3: sintering the molybdenum disulfide precursor at 300° C. to 500° C. under the protection of an argon-hydrogen mixed gas to obtain molybdenum disulfide; S4: mixing the carbon source with the molybdenum disulfide, adding ethylene tar, and sintering at 700° C. to 900° C. under the protection of an argon-hydrogen mixed gas to obtain a sodium ion battery hard carbon-molybdenum disulfide negative electrode material.

2. The method for preparing the hard carbon-molybdenum disulfide negative electrode material for sodium ion battery according to claim 1, characterized in that: The molybdenum source is selected from at least one of ammonium molybdate, magnesium molybdate, lithium molybdate and potassium molybdate.

3. The method for preparing the hard carbon-molybdenum disulfide negative electrode material for sodium ion battery according to claim 1, characterized in that: The sulfur source is selected from at least one of ammonium thiocyanate, ammonium sulfide, sodium sulfide, potassium sulfide, sodium thiosulfate, diallyl sulfide, ethyl mercaptan, propyl mercaptan, and thiophenol.

4. The method for preparing the hard carbon-molybdenum disulfide negative electrode material for sodium ion battery according to claim 1, characterized in that: The solvent is deionized water or ethanol.

5. The method for preparing the hard carbon-molybdenum disulfide negative electrode material for sodium ion battery according to claim 1, characterized in that: The carbon source is selected from at least one of starch, lignin, cellulose and humic acid powder.

6. The method for preparing the hard carbon-molybdenum disulfide negative electrode material for sodium ion batteries according to any one of claims 1 to 5, characterized in that: The molar ratio of the molybdenum source to the sulfur source is in the range of 1:(1-1.5).

7. The method for preparing the hard carbon-molybdenum disulfide negative electrode material for sodium ion battery according to claim 6, characterized in that: The mass ratio of the carbon source to the molybdenum disulfide is in the range of (1-5):

1.

8. The method for preparing the hard carbon-molybdenum disulfide negative electrode material for sodium ion battery according to claim 6, characterized in that: Sintering the molybdenum disulfide precursor at 300° C. to 500° C. includes: heating to 300° C. to 500° C. at a heating rate of 5 to 10° C. / min and sintering for 1 hour.

9. The method for preparing the hard carbon-molybdenum disulfide negative electrode material for sodium ion battery according to claim 6, characterized in that: The sintering at 700° C. to 900° C. in step S4 includes: heating to 700° C. to 900° C. at a heating rate of 5 to 10° C. / min and sintering for 1 hour.

10. A sodium ion battery hard carbon-molybdenum disulfide negative electrode material, characterized in that: The method is used to prepare the sodium ion battery hard carbon-molybdenum disulfide negative electrode material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Carbon-coated molybdenum sulfide / water hyacinth biomass carbon composite material and preparation method and use thereof

    CN109273679A

  • Negative electrode material, preparation method and sodium ion battery

    CN114141986A